I'm Ogre It - Ebbeler, Jeffrey (New York : Holiday House, 2022)
"Izzie and her a new friend, an Ogre named Tim, plan an obstacle course to lure her brother Ollie away from his video game. Ollie is so absorbed in the video game Smash Tower that he doesnt notice that his sister and an ogre named Tim have emptied his room and constructed an obstacle course that mirrors the levels of the game in the yard. But a tell-tale red string leads him to the challenges. This comic is perfect for reintroducing kids to the fun of in-person play."--
Ages 4-8.
Grades 2-3.
Keywords: Ghouls and ogres -- Comic books, strips, etc; Video games -- Comic books, strips, etc; Play -- Comic books, strips, etc; Siblings -- Comic books, strips, etc; Readers (Publications); Graphic novels